An Evaluation On Critical Factors Oftime Performance: Engineering, Procurement And Construction At Senoro Project - Febriana, Mega; Firman, Aries F (The Indonesian Journal of Business Administration, 2014)
Abstract— Sendev Project, operated by Joint Operating Body of Perta – Medgi (PERTACO), has purpose to deliver the gas to the buyer in December 2014. Delay is common in a project, and it is inevitable that it is also occurred in Sendev Project. The delay can be caused by internal and external factors. To overcome the delays, the contribution factors of the delay shall be evaluated first. This study focus on creating a map of the critical factors that give impact to the time or duration of Engineering, Procurement, and Construction (EPC) Sendev Project at Central Processing Plant (CPP) area. The data collection used in this research is the primary data obtained by interviewing five (5) key personnel from PERTACO and secondary data obtained from monthly and weekly reports and weekly of Sendev Project from January to June 2014. The critical factors based on literature were also evaluated toward the Sendev Project. As a result from the data analysis and literature, thirteen (13) factors were identified as critical factors which give impact to the time or duration of Sendev Project which are the manpower sufficiency and productivity, performance of sub-contractors, machine sufficiency, and Project Management Team (PMT) decision-making and authority, construction management strategy, engineering design change, material sufficiency, weather, social awareness, proper planning of the contract, good project implementation, effective risk allocation, and communication. The critical factors will be used as reference to develop the mitigation plan in order to minimize Sendev Project delay. Keywords: project, delay, critical factors, Project Management Team (PMT)